ESTIMATION OF MAIKOP ROCKS OIL-AND-GAS SATURATION OF SUBBOTINA FIELD ACCORDING TO WELL SURVEY COMPLEX - MAKOVETS, O.; KARPENKO, O.; BASHKIROV, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The productive Maykopian deposits of Subbotina oil-and-gas field are the typical for infinite strike and thickness of fissile terrigenous strata of Ukrainian sector of Black Sea shelf. On the structure and geological-geophysical characteristics oil-and-gas reservoirs referred to so-called "complex structure reservoirs". It is necessary to use a new approaches and the methodology intended for eliciting of production ranges, interpretation results uncertainty elimination and accuracy enhancement in obtaining of complex reservoirs bulk properties. Here brought an example of complex realization of available geological-geophysical data with linear discriminant analysis using.